Role of the kidney in regulating plasma immunoreactive beta-melanocyte-stimulating hormone. Issue 6014 (10th April 1976) - Smith, A G; Shuster, S; Thody, A J; Alvarez-Ude, F; Kerr, D N
Abstract : An analysis of the factors that influence the increase in plasma immunoreactive beta-melanocyte-stimulating hormone (beta-MSH) concentration in chronic renal failure showed that: (a) the increase correlated with the increase in serum creatinine concentrations; (b) beta-MSH was not cleared from the plasma by haemodialysis; (c) beta-MSH concentrations increased with length of time on dialysis and increased further after bilateral nephrectomy but there was no further increase with time; (d) beta-MSH levels decreased to normal after renal transplantation; and (e) beta-MSH was excreted in urine only when plasma levels rose to well above those of chronic renal failure (in Nelson's syndrome). These findings suggest that the kidney regulated plasma beta-MSH by a non-excretory mechanism and is the major site of beta-MSH metabolism.